Some Poylphenolic Constituents of Triticum aestivum (Wheat bran, Sakha 69) and Their Antibacterial Effect - Michael, H.N.; Guergues, S.N.; Sandak, R.N. (Asian Journal of Chemistry, 2010)
The polyphenolic constituents of Triticum aestivum (wheat bran, Sakha69) (Gramineae) were investigated through extraction first with acetoneand then with ethyl alcohol. The acetone extract showed to contain 2flavone glycosides, 2 C-glycosides and 2 aglycones, which were identifiedas luteolin-7-0-rutinoside, apigenin-7-0-neohesperidoside, 6,8-di-Cglucosideapigenin, apigenin-6-C-glucoside-7-0-glucoside, apigenin andluteolin. The ethanolic extract proved to contain luteolin-7-glucuronide,7,3'-diglucoside, vitexin, isovitexin, chlorogenic and p-coumaric acids. Allthe isolated and purified components were thoroughly identified usingboth physical and chemical methods of analyses and were further confinnedby the spectral measurements. The antibacterial effect of the twoextracts was studied by using the agar-diffusion technique on six differentstrains of bacteria.